A biomimetic spore nanoplatform for boosting chemodynamic therapy and bacteria-mediated antitumor immunity for synergistic cancer treatment - Cuixia Zheng; Lingling Sun; Hongjuan Zhao; Mengya Niu; Dandan Zhang; Xinxin Liu; Qingling Song; Weijie Zhong; Baojin Wang; Yun Zhang; Lei Wang (Elsevier, 2024)
Bacterial-based antitumor immunity has become a promising strategy to activate the immune system for fighting cancer. However, the potential application of bacterial therapy is hindered by the presence of instability and susceptibility to infections within bacterial populations. Furthermore, monotherapy is ineffective in completely eliminating complex cancer with multiple contributing factors. In this study, based on our discovery that spore shell (SS) of Bacillus coagulans exhibits excellent tumor-targeting ability and adjuvant activity, we develop a biomimetic spore nanoplatform to boost bacteria-mediated antitumor therapy, chemodynamic therapy and antitumor immunity for synergistic cancer treatment. In detail, SS is separated from probiotic spores and then attached to the surface of liposome (Lipo) that was loaded with hemoglobin (Hb), glucose oxidase (GOx) and JQ1 to construct SS@Lipo/Hb/GOx/JQ1. In tumor tissue, highly toxic hydroxyl radicals (•OH) are generated via sequential catalytic reactions: GOx catalyzing glucose into H2O2 and Fe2+ in Hb decomposing H2O2 into •OH. The combination of •OH and SS adjuvant can improve tumor immunogenicity and activate immune system. Meanwhile, JQ1-mediated down-regulation of PD-L1 and Hb-induced hypoxia alleviation synergistically reshape immunosuppressive tumor microenvironment and potentiate immune response. In this manner, SS@Lipo/Hb/GOx/JQ1 significantly suppresses tumor growth and metastasis. To summarize, the nanoplatform represents an optimum strategy to potentiate bacteria-based cancer immunotherapy.